Analisis Konten Visual dalam Promosi Pariwisata Buton Tengah di Media Sosial Instagram Visitbuteng - Salman, Aan; Suherman, Ansar; Hidayatullah, Muh. (JOPPAS: Journal of Public Policy and Administration Silampari, 2025)
This study analyzes the visual content the Instagram account @visitbuteng uses to promote tourism destinations in Central Buton. The research method used in this study is a qualitative approach, explaining the analysis of visual content in promoting tourism in Central Buton on the Instagram account @visitbuteng. The results indicate that visual content analysis conducted through specific content placement and tourism activities on Instagram, the website, and YouTube is practical and can generate positive feedback and rapid responses. However, promoting tourism destinations in Central Buton on Instagram via @visitbuteng is ineffective if it only uploads daily content or reposts other content. A better visual content strategy is needed to maximize tourism promotion through Instagram.   Keywords: Visual Content, Central Button Tourism Promotion, Instagram Social Media